Reevaluation of Blapimorpha and Opatrinae: addressing a major phylogeny‐classification gap in darkling beetles (Coleoptera: Tenebrionidae: Blaptinae). (16th September 2020) - Kamiński, Marcin J.; Lumen, Ryan; Kanda, Kojun; Iwan, Dariusz; Johnston, M. Andrew; Kergoat, Gael J.; Bouchard, Patrice; Bai, Xing Long; Li, Xiu Min; Ren, Guo Dong; Smith, Aaron D.
Abstract: The taxonomic concepts of Blapimorpha and Opatrinae (informal and traditional, morphology‐based groupings among darkling beetles) are tested using molecular phylogenetics and a reassessment of larval and adult morphology to address a major phylogeny‐classification gap in Tenebrionidae. Instead of a holistic approach (family‐level phylogeny), this study uses a bottom‐up strategy (tribal grouping) in order to define larger, monophyletic lineages within Tenebrioninae. Sampling included representatives of 27 tenebrionid tribes: Alleculini, Amarygmini, Amphidorini, Blaptini, Bolitophagini, Branchini, Cerenopini, Coniontini, Caenocrypticini, Dendarini, Eulabini, Helopini, Lagriini, Melanimini, Opatrini, Pedinini, Phaleriini, Physogasterini, Platynotini, Platyscelidini, Praociini, Scaurini, Scotobiini, Tenebrionini, Trachyscelini, Triboliini and Ulomini. Molecular analyses were based on DNA sequence data from four non‐overlapping gene regions: carbamoyl‐phosphate synthetase domain of rudimentary (CAD) (723 bp), wingless ( wg ) (438 bp) and nuclear ribosomal 28S (1101 bp) and mitochondrial ribosomal 12S (363 bp). Additionally, 15 larval and imaginal characters were scored and subjected to an ancestral state reconstruction analysis. Results revealed that Amphidorini, Blaptini, Dendarini, Pedinini, Platynotini, Platyscelidini and Opatrini form a clade which can be defined by the following morphological features: adults—antennae lacking compound/stellate sensoria; procoxal cavities externally and internally closed, intersternal membrane of abdominal ventrites 3–5 visible; paired abdominal defensive glands present, elongate, not annulated; larvae—prolegs enlarged (adapted for digging); ninth tergite lacking urogomphi. To accommodate this monophyletic grouping (281 genera and ∼4000 species), the subfamily Blaptinae sens. nov. is resurrected. Prior to these results, all of the tribes within Blaptinae were classified within the polyphyletic subfamily Tenebrioninae. The non‐monophyletic nature of Terebrioninae has already been postulated by previous authors, yet no taxonomic decisions were made to fix its status. The reinstatement of Blaptinae, which groups ∼50% of the former Tenebrioninae, helps to clarify phylogenetic relations among the whole family and is the first step towards a complete higher‐level revision of Tenebrionidae. The Central Asian tribe Dissonomini (two genera, ∼30 species) was not included in Blaptinae due to a lack of representatives in the performed phylogenetic analyses; however, based on morphological features, the tribe is listed as a potential addition to the subfamily. Abstract : The concept of Blaptinae (=Opatrinae) has traditionally been recognized by many previous researchers; however, the formal designation of this group was previously suppressed due to a lack of concrete evidence. Amphidorini, Blaptini, Dendarini, Pedinini, Platynotini, Platyscelidini and Opatrini form a clade supported by molecular data. To accommodate this monophyletic grouping (281 genera, ∼4000 species) the subfamily Blaptinae is resurrected. Two main clades were recovered within Blaptinae, the 'blaptoid' clade (Amphidorini, Blaptini, Platyscelidini) and 'opatrinoid' clade (Dendarini, Pedinini, Platynotini and Opatrini).